Melatonin Reduces Apoptosis Resistance of Hepatocellular Carcinoma Cells by Inhibiting BMAL1 - Anqi Wang MMed; Bei Zhou MMed; Yue Zhu MD; Chaisheng Tan MMed; Jing Xu MD; Jie Cui PhD; Li Zhang MMed; Guoping Sun PhD (Integrative Cancer Therapies, 2022)
Purpose: This study aimed to explore the role and molecular mechanism of brain and muscle ARNT-like protein 1 (BMAL1) in hepatocellular carcinoma (HCC), and the effect of melatonin on BMAL1 expression and apoptosis of HCC cells. Methods: We mainly used immunohistochemistry, western blot, cck-8 assays, flow cytometry, wound-healing assay, transwell assay, and RT-qPCR for this research. Results: The expression of BMAL1 protein was frequently up-regulated in the tissues and cell lines of HCC patients. Its high expression was significantly associated with tumor size, tumor differentiation degree, and shorter survival. In addition, cell functional experiments showed that BMAL1 could promote proliferation and migration, and inhibit apoptosis in HCC cell lines. Furthermore, the expression of BMAL1 was related to the endoplasmic reticulum stress (ERS) level. Knockdown of BMAL1 could inhibit the expression of ERS-related protein, while overexpression of BMAL1 led to the increase of ERS-related protein’s level. Low concentration of ERS led to the increase of BMAL1, and a certain degree of ERS in turn inhibited the expression of BMAL1. Melatonin promoted apoptosis of hepatoma cells by inhibiting the expression of BMAL1. Conclusion: BMAL1 plays a key role in HCC patients’ survival and tumor growth, which may be related to its interaction with ERS-related pathways. Melatonin can regulate ERS-related apoptosis resistance by inhibiting BMAL1 expression, promoting apoptosis of HCC cells.